Democracia popular, sem eleições nem políticos - Rudas, Sebastián (Veritas (Porto Alegre), 2021)
LANDEMORE, Hélène. Open Democracy. Reinventing Popular Rule for the Twenty-First Century. New Jersey: Princeton University Press, 2020.